The axiomatization (taq‘id) of the critical method (Manhaj al-Naqd) of hadith scholars: responding to anti-intellectualism - Safi, Mohammed Tayssir (Penerbit Universiti Kebangsaan Malaysia, 2023)
The Criteria of Authenticity (shurut al-sihha), as a set of rules (qawa‘id), has in recent years come under severe scrutiny by contemporary hadith scholarship. This article will investigate one line of criticism which rejects the goal of developing theoretical rules(al tanzir) altogether, and instead encourages the applied work (al-tatbiq) of analyzing Prophetic statements. This article will provide an epistemic analysis of the objection which situates it within a broadly anti-intellectualist framework. I will then respond to the objection by suggesting a different conception (tasawwur) of qawa‘id and then arguing that the relationship between knowledge of theoretical rules, and knowledge in the form of skills or abilities, helps rebut, or at least weakens their objection. Finally, I will show that the critical method (manhaj al-naqd) of hadith scholars is an epistemic apparatus (ala ma‘rifiyya), which aids those who apply it, in reasoning properly and protects them from making errors in epistemic judgement.